A computationally inexpensive algorithm for determining outer and inner enclosures of nonlinear mappings of ellipsoidal domains - Rauh, Andreas; Jaulin, Luc (Zielona Góra: Uniwersytet Zielonogórski)
A wide variety of approaches for set-valued simulation, parameter identification, state estimation as well as reachability, observability and stability analysis for nonlinear discrete-time systems involve the propagation of ellipsoids via nonlinear functions. It is well known that the corresponding image sets usually possess a complex shape and may even be nonconvex despite the convexity of the input data.
Keywords: bounded uncertainty; guaranteed enclosures; ellipsoidal enclosures; inner and outer approximations; nonlinear systems; confidence intervals